Peningkatan Kapasitas Peternak Sapi Bali Dalam Pengolahan Pakan Fermentasi Di Kel. Malino, Kec. Tinggimoncong, Kab. Gowa, Sulawesi Selatan - Said, Muhammad Irfan; Syawal, Sutomo; Asriany, Anie (Universitas Mataram, 2024)
Increasing livestock productivity can be done through efforts to improve livestock nutrition and environment. The basic problem faced by partners is a lack of feed in certain seasons and the production of quite large amounts of fecal waste. In this case, universities, as one of the institutions responsible for providing solutions, of course feel the need to take